Analyzing the Determinants of Audit Report Lag: The Role of Earning Volatility, Audit Quality, and Auditor Industry Specialization - Dika Puspitaningrum (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study examines the factors influencing audit report lag (ARL), focusing on the impact of earning volatility (EV), audit quality (KA), and the moderating role of auditor industry specialization. Using secondary data from non-consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022, 52 observations were selected through purposive sampling. Results show that EV negatively and significantly affects ARL (coefficient = -12.641, p = 0.043), while KA has no significant effect (coefficient = -6.102, p = 0.7350). Additionally, auditor industry specialization does not moderate the relationships between EV and ARL (coefficient = 5.623, p = 0.520) or KA and ARL (coefficient = 4.677, p = 0.876). These findings highlight the importance of earnings volatility in reducing ARL and suggest that audit quality and auditor specialization play limited roles. The study provides insights for improving financial reporting timeliness and recommends future research to expand sample coverage and refine measurement proxies.